Модель и метод иерархического управления запросами в гибридной сети доставки контента - Евсеева, О. Ю.; Кадер, М. Б. (My University, 2014)
Переход к гибридным сетям доставки контента (НCDN) позволяет сочетать низкую стоимость услуг с высоким их качеством, однако требует соответствующих методов управления, в том числе и управления запросами. В работе предлагаются два варианта потоковой математической модели управления запросами, предполагающие использование для их обслуживания разного количества CDN-серверов. Особенность предлагаемого подхода состоит в учете состояния нижележащей транспортной инфраструктуры при решении задач управления запросами. За счет введения в модель QoS-ограничений удается обеспечить гарантии по качеству доставки на сетевом уровне, а за счет выбора критерия оптимальности все типы ресурсов (вычислительные ресурсы серверов и канальные ресурсы трактов передачи транспортной сети) используются сбалансированно. A key challenge for infocommunication networks including Internet is delivering large-scale content of different types to growing number of users. Content Delivery Networks (CDN) and Peer-to-Peer (P2P) networks are two dominant architectures that can be implemented. But CDN P2P-Hybrid architecture (HCDN), that is integrating P2P and CDN features, promises to combine their advantages and to achieve maximal effectiveness of content distribution with guaranteed quality of service and relatively low cost. At same time HCDN needs appropriate management practices for solving different problems where request routing is one of. In order to maximize the effectiveness of content delivering to the user, to provide guaranteed quality of services and to use of resources in effective way method for request routing in HCDN should be based on a rigorous mathematical justification. This article offers two flow-based mathematical models which allow servicing the request by using different number of CDN-servers for content sourcing and turn the request routing task into optimization problem. By downloading from several CDN-servers use of computing and network resources becomes balanced that contribute to the result quality of service improving. Mathematically load-balancing is achieved by choice of the optimality criterion. A distinctive feature of the proposed approach is related to taking into account state of the underlying transport infrastructure. It allows to solve the problem of request routing on HCDN and traffic routing problem in transport telecommunication network jointly. The models contain tensor QoS-restrictions satisfaction of which guarantees on the quality of delivery at the network level within transport network. According to offered models hierarchical two layers control method for request routing on HCDN is proposed.
Keywords: доставка контента; управление запросами